Coating minimally processed Golden Nam Dok Mai mango with Aloe vera gel extract to maintain quality during storage - Suwapanich, Rachit; Thompson, Anthony Keith; Nukthamna, Pikunthong (My University, 2025)
This study investigated the effects of varying concentrations of Aloe vera gel extract on the post-harvest quality and shelf life of minimally processed 'Golden Nam Dok Mai' mango chunks stored at 5 °C for 7 days. Although all mango chunks softened during storage, slower softening was observed with higher Aloe vera concentrations, except for those treated with 100% A. vera, which showed similar softening to the controls. Coating with A. vera gel reduced weight loss compared to untreated controls, although the concentration of A. vera did not significantly influence weight loss. Total soluble solids increased across all treatments, but 40% A. vera treatment led to the least increase, suggesting moderate metabolic activity. Titratable acidity decreased during storage, with higher A. vera concentrations (40% and 60%) preserving acidity better. Vitamin C content was better retained in mango chunks coated with 100% A. vera. Additionally, A. vera coatings led to a darker flesh over time, particularly with thicker coatings. Sensory evaluation revealed that mango chunks coated with 40% A. vera gel were most preferred. We concluded that coating minimally processed ‘Golden Nam Dok Mai’ mango chunks with A. vera gel would be beneficial in terms of a cost-effective natural preservative to enhance the shelf life and sensory qualities of fresh-cut mangoes.
Keywords: Aloe vera gel; edible coating; mango (minimally processed); mango preservation